Edukasi Manajemen Kesehatan Remaja Saat Menstruasi di SMP N 5 Kota Jambi - Nel Efni; Tina Yuli Fatmawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The obligation to maintain health and hygiene related to menstruation is almost ignored by many people. Many factors that cause it, can be due to ignorance or due to lack of education from schools and parents. Many girls do not have a proper understanding that their menstruation is a normal biological process and they only know it at menarche. Insufficient knowledge about menstruation, menstrual cycle and Menstrual Hygiene Management (MKM) during menstruation can result in problems during menstruation such as dysmenorrhea, pelvic muscle cramps. This community service was carried out at the SMP N 5 Jambi City, with the aim that students could understand how to maintain cleanliness during menstruation. so that adolescents will be free from diseases, especially those related to reproductive health. The service method applied by the community service team is discussion, guidance, and persuasive communication. Held in December 2020-January 2021. After the counseling activities were carried out, all the teenagers who attended understood about treatment during menstruation